Synergy of Digital and Financial Literacy in Building a Resilient Financial Ecosystem in Indonesia - Ahmad Wahyudin; Faisol Faisol; Ugroseno Damara Prasadhana Handoyo (Jurnal Riset Ekonomi dan Akuntansi, 2026)
This study aims to analyze the relationship between digital literacy and financial literacy in strengthening a resilient and inclusive national financial ecosystem in Indonesia. As the financial landscape increasingly shifts toward digitalization, the integration of technological competence and financial awareness becomes a critical factor in ensuring economic stability and inclusive growth. Using a quantitative research approach, data were collected from 200 active users of digital financial services through a structured questionnaire. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test the validity, reliability, and causal relationships among variables. The results reveal that both digital literacy and financial literacy have a positive and significant influence on the development of a robust and inclusive financial ecosystem. Furthermore, the interaction between these two literacies strengthens individuals’ ability to make informed financial decisions, utilize digital platforms effectively, and contribute to financial inclusion. The findings highlight that the synergy between digital and financial literacy is essential for creating a sustainable financial system capable of adapting to technological disruption and economic uncertainty. This study contributes theoretically by integrating digital literacy into financial inclusion models, and practically by emphasizing the importance of joint initiatives among government, financial institutions, and educational organizations in promoting literacy-based empowerment. In conclusion, enhancing digital and financial literacy simultaneously is a strategic step toward building an inclusive, secure, and resilient financial ecosystem in the digital era.